Spectral preferences of Lycorma delicatula (Hemiptera: Fulgoridae). Issue 2 (20th March 2013) - Jang, Yikweon; An, Hyon‐Gyong; Kim, Hyojoong; Kim, Kwang‐Ho
Abstract Many insects prefer lights with certain spectral properties, and such preferences may be associated with behavioral contexts such as mating, host finding or dispersal. Lycorma delicatula (Hemiptera: Fulgoridae) is a newly invasive species in Korea and is spreading rapidly. It is diurnal and may rely on visual cues for orientation. We conducted a series of three phototaxis experiments to understand spectral preferences in L. delicatula: light/dark choice, UV/white light choice, and color preference experiments. Nymphs of the third and final stages as well as adults were used for these experiments. In the light/dark choice, the orientation of L. delicatula was bimodal between the white light and darkness, for all stages and both sexes. In a choice of UV (395–410 nm wavelengths) vs. white light, L. delicatula of both sexes and all stages preferred the UV light. In the color preference experiment where insects had a choice of four colors in a circular arena, L. delicatula stayed significantly longer in the blue light than in white, yellow or green lights. Overall, nymphs and adults of L. delicatula oriented toward lights with shorter wavelengths, and this orientation was consistent throughout all stages, regardless of sex. It is necessary to investigate the behavioral contexts under which L. delicatula prefers the UV and blue lights.